Correlation between the Frequency of Th17 Cell and the Expression of MicroRNA-206 in Patients with Dermatomyositis. (30th October 2013) - Tang, Xinyi; Tian, Xinyu; Zhang, Yue; Wu, Wei; Tian, Jie; Rui, Ke; Tong, Jia; Lu, Liwei; Xu, Huaxi; Wang, Shengjun
Abstract : It was reported that IL-17 had been detected in the inflammatory infiltrates of patients with DM (dermatomyositis). In this study, we investigated the frequency of Th17 cells and the expression of microRNA-206 (miR-206) in DM patients. Firstly, we observed that the frequency of Th17 cells and the expression of transcription factors were increased significantly in the PBMCs of DM patients. Secondly, we found that there was a positive correlation between the percentages of Th17 cells and serum level of CK in DM patients. And the serum concentrations of IL-6, IL-1 β, TGF- β, and IL-23, the important cytokines of Th17 differentiation, were increased in DM patients. It was predicted that Krüppel-like factor 4 (KLF4) is one of the multiple targets of miR-206. We detected the expression of miR-206 in DM patients, and it was decreased in the serum and PBMCs of DM patients. The augmented expression of KLF is accompanied by the attenuated expression of miR-206. Furthermore, a negative correlation between the percentages of Th17 cells and the expression of miR-206 in DM patients has been found. Taken together, these findings suggest the attenuated expression of miR-206, and the augmented frequency of Th17 cells in DM patients.